INFLUENCE CURRENT RATIO, PRICE EARNINGS RATIO, RETURN ON EQUITY, DEBT TO EQUITY RATIO, NET PROFIT MARGIN AND TOTAL ASSETS TURNOVER AGAINST COMPANY SIZE (Jurnal Ipteks Terapan, 2023)
The aim of this research is to determine the influence of independent variablesCurrent Ratio (CR), Price Earning Ratio (PER), Return On Equity (ROE), Debt to Equity Ratio (DER), Net Profit margins, Total Assets Turnovers (TATTOO) to variables Company Size depends on companies operating in the field food and drink Which registered in BEI 2018-2020. The test results are only the Debt to Equity Ratio variable influential in a way Partial And significant to size company whereas variables Current Ratio, Price Earning Ratio, Return on Equity, Net Profit Margin and Total Asset Turnover has no partial and insignificant influence on size company on food And drink Which registered in BEI 2018-2020, while simultaneously Current Ratio, Price Earning Ratio, Return on Equity, Debt to Equity Ratio, Net Profit Margin, Total Asset Turnover have an influence and are significant to size company on company food And drink Which registeredon BEI 2018-2020